Fuzzy algorithms applied to the comparative evaluation of crossroad designs - Largueche, Oualid; Lallam, Mostefa; Driss, Miloud; Hamadouched, Mohammed Amine (Vojnotehnički glasnik / Military Technical Courier, 2026)
Introduction/purpose: Urban traffic crossroads represent highly complex nodes within transportation networks due to the convergence of multiple, often conflicting, traffic streams. Managing these competing flows poses significant challenges, leading to issues such as fluctuating delays and backflow, particularly at supersaturated intersections. Given that these crossroads frequently act as bottlenecks, accurate short-term traffic flow predictions are crucial for effective planning and congestion mitigation. This study aims to propose a robust, multi-criteria evaluation framework for crossroad design to support optimized urban planning and traffic management.Methods: To address the inherent complexities and uncertainties associated with evaluating such designs, this research employs the Fuzzy Analytic Hierarchy Process (FAHP). This method is particularly suited for contexts in which expert judgments, often involving qualitative criteria such as landscape integration and local economic impact, lack absolute precision. Our approach integrates fuzzy logic to manage the subjective and imprecise nature of these evaluations, alongside quantitative factors such as cost and traffic saturation. Based on an extensive literature review and established disciplinary standards in traffic engineering and urban planning, we developed a comprehensive grid of 32 criteria and sub-criteria. These criteria cover key aspects such as road safety, service level, and traffic flow. Experts then assign weights to these criteria, which are processed through FAHP to produce a global performance indicator. This indicator allows the ranking and comparison of different alternative designs.Results: The application of this FAHP-based framework yields a global performance indicator that facilitates the objective ranking of alternative crossroad designs. The methodology provides a structured approach to balance multiple, often conflicting, criteria in complex decision environments. The practical relevance of this method is demonstrated through a case study of the Chettia junction, where it successfully identifies the optimal configuration among several proposed alternatives. This underscores FAHP's versatility in evaluating performance within intricate urban systems.Conclusion: This study successfully situates FAHP within a broader Multi-Criteria Decision Analysis (MCDA) framework, offering an original application to crossroad design. By integrating fuzzy logic, it effectively manages the uncertainty associated with both qualitative and quantitative evaluation criteria, proving particularly valuable when precise expert judgments are diffucult for experts to provide. The proposed framework provides a robust and multidimensional evaluation tool for urban planners and traffic engineers, enabling more informed and optimized infrastructure decisions for complex urban intersections.
Keywords: crossroad; Fuzzy Analytic Hierarchy Process (FAHP); design alternatives; criteria; level of service; comprehensive performance indicator (CPI)